Quantitative kinematics of a frictional viscous lowangle normal fault on Kea (Western Cyclades, Greece) - Müller, M.; Grasemann, B.; Iglseder, C.; ACCEL, Team (TRABAJOS DE GEOLOGÍA, 2010)
Lithospheric extension during the Miocene is well documented in the Aegean. Within theCentral and Western Cyclades extension has been documented in detail by the formation ofMetamorphic Core Complexes and movement along low-angle normal faults (LANFs). Focusing on ahitherto unrecognised main low-angled fault geometry outcropping on northern Kea, this work presentspervasive evidence of top-to-south kinematics.